The Eastern Shore spessartite dykes, Nova Scotia, Canada: A glimpse into the subcontinental lithospheric mantle under the Meguma terrane - Nickerson, Shae J.; White, Chris E.; Barr, Sandra M.; Archibald, Donnelly B. (Atlantic Geoscience, 2025)
The ca. 370 Ma Eastern Shore dykes include six single or multiple (two or three) parallel spessartite dykes that trend NNW in the Sheet Harbour area of eastern mainland Nova Scotia. Spessartite is a variety of calc-alkaline lamprophyre that characteristically occurs in dykes associated with granitoid rocks and gold mineralization in orogenic belts. Spessartite dykes typically contain crustal xenoliths and xenocrysts, a feature shown by three of the Eastern Shore dykes (Popes Harbour, Tuff Island, and Borgles Island). The Eastern Shore dykes are mineralogically and chemically typical of spessartite but show wide chemical variation and higher MgO, lower TiO2 and P2O5, and flatter chondrite-normalized rare-earth-element patterns than are typical of spessartite. The pair of dykes at Sober Island show internal variations that are evidence of magma evolution resulting from plagioclase and amphibole fractionation; the East Jeddore and Little Harbour Road and Coast dykes are similar to the least evolved Sober Island spessartite. The three xenolith/xenocryst-bearing dykes show anomalous chemical features such as more enrichment in light rare-earth elements (REE), higher Sr, Y, Zr, and Hf, and more varied compositions compared to the other dykes. The Popes Harbour dyke is characterized by low Ni. Despite these differences, mainly parallel chondrite-normalized REE patterns suggest that the Eastern Shore dykes are related and derived from hydrous large-ion-lithophile- and high-field strength-element-enriched garnet-bearing mantle-derived magma that experienced variable crustal contamination.